2022
DOI: 10.1111/1365-2435.14083
|View full text |Cite|
|
Sign up to set email alerts
|

Environment, taxonomy and morphology constrain insect thermal physiology along tropical mountains

Abstract: 1. Tropical mountains display limited variation in monthly temperatures, but high spatial climatic variability. It is assumed this stability promotes ecological and physiological adaptations to local temperatures, which may preclude dispersal up or downslope. Determining how environmental, taxonomic and morphological factors affect thermal limits is fundamental to understand biotic responses to global warming. 2. We selected 54 species of dragonflies and damselflies (Order Odonata) distributed from 300 to 2,55… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 105 publications
1
10
0
Order By: Relevance
“…We found that non-forest-dependent species generally have larger range sizes than forest-dependent species, similar to the pattern reported in the tropical Andes, where nonforest species occupy larger elevation ranges compared to forest-dependent species [84]. This is likely due to forest-dependent species being more specialized [41][42][43] than open-area species which can reproduce in a wide variety of broadly available habitats. We classified 43.4% (221 species) as unable to have lasting populations in the absence of a lotic habitat.…”
Section: Are There Differences In Diversity Patterns Shown By Forest ...supporting
confidence: 79%
See 1 more Smart Citation
“…We found that non-forest-dependent species generally have larger range sizes than forest-dependent species, similar to the pattern reported in the tropical Andes, where nonforest species occupy larger elevation ranges compared to forest-dependent species [84]. This is likely due to forest-dependent species being more specialized [41][42][43] than open-area species which can reproduce in a wide variety of broadly available habitats. We classified 43.4% (221 species) as unable to have lasting populations in the absence of a lotic habitat.…”
Section: Are There Differences In Diversity Patterns Shown By Forest ...supporting
confidence: 79%
“…We expected lentic species to have larger range sizes, as hypothesized by [40]. Similarly, forest species are expected to have smaller ranges than non-forest-dependent ones since they are highly specialized [41][42][43] in patchy distributed habitats.…”
Section: Functional Traits and Conservation Statusmentioning
confidence: 99%
“…Here, we used the total area encompassed by all of the species' occupied grid cells from the presence/absence matrix that we generated (Rotenberry & Balasubramaniam, 2020). Second, we also sought to account for features of a species' thermal biology because species that are adapted to the cold are likely capable of living at higher elevations (Bota‐Sierra et al, 2022; Sheldon et al, 2018). Data on direct measurements for species' thermal physiology are available for only a small number of dragonflies (Bennett et al, 2018), and so we instead used the average temperature that a species encounters across its geographic range as a continuous proxy of whether the species is relatively adapted to cold or warm conditions (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…We included the mean annual temperature across a species' range to control for the expectation that cold-adapted species are likely to be found at higher elevations (e.g. Bota-Sierra et al, 2022). Because elevation can also filter animal species based on body size (e.g.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…temperature, humidity). The role that such factors play in establishing the elevational distributions of tropical montane species has been increasingly studied, partly owing to an interest in forecasting species responses to climatic change (Sheldon et al, 2011; García-Robledo et al, 2016; Slatyer & Schoville, 2016; Zuloaga & Kerr, 2016; Freeman et al, 2018; Linck et al, 2021; Bota-Sierra et al, 2022). Because of their narrow elevational ranges and often abrupt replacement of closely related species along mountain slopes, tropical birds have been a model system for the study of elevational range limits (Terborgh, 1971; Diamond, 1973; Sheldon et al, 2011; Jankowski et al, 2013; Londoño et al, 2015; Freeman et al, 2019; 2022).…”
Section: Introductionmentioning
confidence: 99%